Midterm experience of Scarf osteotomy as a new technique in a General Orthopaedic Department. (September 2019) - Samaras, Dimitrios; Gougoulias, Nikolaos; Varitimidis, Sokratis; Hantes, Michael; Karachalios, Theofilos; Malizos, Konstantinos; Dailiana, Zoe
Highlights: Scarf osteotomy is a demanding technique. Prepare for perioperative complications and try to avoid them. Correct all the deformities of the forefoot, not only the first ray. Abstract: Scarf osteotomy has become popular as a versatile procedure that could correct most cases of hallux valgus. The purpose of this study is to report the experience with scarf osteotomy performed as a new technique by different surgeons of a general orthopaedic department. This study reviewed the outcome of 67 patients with 78 feet with hallux valgus deformity treated by scarf osteotomy at our institution, with an average follow-up of 24 months (12–84). Results were analyzed by clinical examination, a questionnaire including the American Orthopaedic Foot and Ankle Society (AOFAS) forefoot score and plain radiographs. The mean AOFAS score increased from 35 points (range, 15–50) preoperatively to 87 points (range, 73–100) at the final follow-up. The radiological angles Hallux Valgus Angle (HVA), 1–2 Intermetatarsal Angle (IMA) and Tibial Sesamoid Position (TSP) improved significantly. Among the 7 recurrences and 15 complications recorded, seven required an additional procedure. Multiple potential pitfalls can occur with scarf osteotomy. Although soft tissue dissection is relative extensive, adherence to careful technique and endurance to the learning curve can produce effective radiological correction of hallux valgus and good clinical results. Level of clinical evidence: III.